An approach for degradation of grape seed and skin proanthocyanidin polymers into oligomers by sulphurous acid. (1st August 2018) - Luo, Lanxin; Cui, Yan; Cheng, Jinhui; Fang, Bairui; Wei, Zongmin; Sun, Baoshan
Highlights: Grape seed and skin PPCs were first degraded into 13 individual OPCs by H2 SO3 . Degradation OPCs was separated into individual procyanidins by HSCCC and Prep-HPLC. The proposed method could be used for the valorization of PPCs in grape seed and skin. The proposed method would be also applicable for the degradation of other plant PPCs. Abstract: To develop an efficient method for degradation of grape seed and skin proanthocyanidins polymers into oligomers, an optimized sulphurous acid degradation conditions for grape seed with the temperature of 60 °C, reaction time of 60 min and sample-sulphurous acid ratio of 1:0.2, and for grape skin with the temperature of 40 °C, reaction time of 60 min and sample-sulphurous acid ratio of 1:0.2, were established. Afterwards, HSCCC and prep-HPLC were used to fractionate and isolate individual proanthocyanidin oligomers from the degradation products. Total of ten dimeric or trimeric procyanidins were obtained, and most of them presented high yield (from 0.7 mg to 13.6 mg per run in grape seed and from 0.5 mg to 4.1 mg per run in grape skin) and high purity (over 90%). The proposed method provides a new way for large preparation of oligomeric proanthocyanidins from naturally abundant and wasted polymeric ones.